Estafette of drift resonances in tokamak configuration with reversed-shear - Ivko, S.V.; Shishkin, A.A. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
Induced particle transport by applying perturbations of the magnetic field with low poloidal “wave” numbers is studied by means of computer simulations. Reversed-shear operation regime for tokamaks is considered. The dependence of drift rotational angle transform profile on particle energy is calculated. The range of particle energies corresponding to reversed shear profile is defined. The removal of helium test particle from the plasma core to the periphery is demonstrated. Метод управления переносом частиц под действием магнитных возмущений с малыми тороидальными волновыми числами изучаен посредством численного моделирования. Рассмотрен режим работы токамака с обращенным широм. Исследована зависимость профиля угла дрейфового прокручивания от энергии частицы. Определен диапазон энергий, соответствующих профилю угла дрейфового прокручивания с обращенным широм. Продемонстрирован вывод тестовой частицы гелия из центра плазмы на периферию.
Keywords: управление движением частиц; эстафета дрейфовых резонансов; токамак с обращенным широм; уравнения ведущего центра; компьютерное моделирование; particle motion control; estafette of drift resonances; reversed shear tokamak; guiding center equations; computer simulation